RANCANG BANGUN SISTEM INFORMASI TABLE SERVICE BERBASIS MOBILE DENGAN MENGGUNAKAN METODE AGILE - rudi budi agung; Wandri Wandri; Marisa Marisa; Hendra Setiawan; Iwan Jaya (Fakultas Teknik dan Ilmu Komputer (FASTIKOM) UNSIQ, 2023)
When evoria all transactions via the internet, the newly growing MSMEs are no exception utilizing this information technology to make transactions and assist in their operational processes. Kedai Jahe 22 is no exception, which is one of the UMKM in the city of Bekasi which quickly applies for orders when the customer is already at the table (table service). This shop previously faced problems recording customer orders manually which caused delays and misunderstandings. To overcome this problem, an Android-based Point of Sale (POS) system with table service was implemented with the help of Agile methods. Test results show that this system has good performance, enabling Kedai Jahe 22 to improve operational efficiency and service to customers. The use of smartphone technology in the culinary business has helped increase customer satisfaction and profits for the shop.